The Impact of Economic Sanctions on Oil Industry: A Case Study of Libya Using the Synthetic Control Method - Ertimi, Basem; Oqab , Basem (Journal of Pure & Applied Sciences, 2022)
This study assesses the impact of economic sanctions on oil exports and economic growth through case studies of Libya. By setting up a synthetic group method that reproduces the oil exports and economic growth of the case study before the imposition of economic sanctions, we compare the oil exports and the economic growth of the Synthetic and the actual for each period. We address a crucial gap in the literature of sanction in a petrostate case study using the synthetic control approach. Our analysis found that both petroleum exports and economic growth were lower with economic sanctions. This research is integrated into the comparative and international landscape of international influence relations with the domestic economy. Economic sanctions, the results show, are the key driver in fluctuations in oil exports and economic growth that might be represented in the oil curse. We believe that our empirical research can contribute to domestic and international policy formation by sanctioned countries. Overall, the findings confirm that sanctions may be imposed on Libya as another channel of the resource curse from the global and foreign policy perspectives.